Virusinfektionen in der Gynäkologie - Aktuelle Entwicklungen bei humanen Papillomviren und Herpesviren - Nagel, Angela; Knöll, Antje (gynäkologische praxis, 2020)
Human papillomavirus (HPV) and herpes simplex virus (HSV) infections are the most common sexually transmitted viral diseases. Prophylactic measures such as HPV vaccination and behavioural precautions for genital herpes are the most promising strategies to prevent these viral infections. The HPV vaccine is safe, immunogenic and effective in the prevention of HPV-associated tumors, but the vaccination rate is far too low in Germany. Cervical cancer is comparatively rare in Germany today and the incidence rate of new cases has been stagnating at a low level for years. Since a persistent hrHPV infection is necessary for the development of cervical cancer, the cervical cancer screening program was modified in January 2020. For women aged 35 years and older, an HPV cervical smear test is now performed in addition to cytology and the screening interval has been extended to three years. The test algorithm for younger women has not been changed. For genital HSV infections, aciclovir-based therapy regimens are recommended, prophylactic or therapeutic vaccines will not be available in the near future. Therefore, information of the patient about the specifics of the disease (such as the often asymptomatic virus shedding) and initiation of an appropriate therapy are decisive for the reduction of the HSV transmission risk and for the treatment success.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Cervical carcinoma screening; Genital infections; Herpes simplex virus; HPV vaccine; Human papillomavirus